THE ROLE OF LOCAL WISDOM IN ETHNOMUSICOLOGICAL EDUCATION FOR CULTURAL IDENTITY FORMATION: A LITERATURE-BASED CONCEPTUAL ANALYSIS: THE ROLE OF LOCAL WISDOM IN ETHNOMUSICOLOGICAL EDUCATION FOR CULTURAL IDENTITY FORMATION: A LITERATURE-BASED CONCEPTUAL ANALYSIS - Yohana, Berthanica; Safrina, Rien; Yetti, Elindra (International Journal of Performing Arts (IJPA), 2024)
Amidst the pressures of globalization, schools often struggle to balance the demand for globalcompetencies with the preservation of local culture. In music education, the dominance of a Westerncentric curriculum can alienate students from their own musical traditions. This paper utilizes aliterature review method to analyze how an ethnomusicological approach, grounded in localwisdom, can serve as a pedagogical alternative to strengthen students' cultural identity. Bysynthesizing various studies, we argue that local wisdom (which includes the social context, function,and philosophy of music) should be the core of learning, not just supplementary material. Theanalysis suggests that engaging students with music from their own cultural environment has thepotential to support identity formation in three aspects: personal (connecting with heritage),collective (strengthening a sense of community), and intercultural (understanding other culturesthrough the lens of one's own). We conclude that applying this approach could shift the function ofthe music classroom from a mere technical training space to one of cultural dialogue. The practicalimplication points to the need to review curriculum design and teacher training to be more orientedtowards local cultural contexts, in order to foster students who have a deep understanding of theirown roots while being open to the world.